The effect of wet cupping on physiological variables and the numerical achievement of elite runners in intermediate distances - Salameh, H.; Qadoume, A.; Abualia, M. (Journal of Physical Education and Sport, 2023)
Wet cupping is one of the alternative medicine methods recommended by Islam and which used in sport recently as an influential and important factor in sports performance. Recently, players have increased interest in wet cupping as a therapeutic method, as well as in improving athletic performance. objectives: The study target is to figure out if the wet cupping (Hijama) affected some physiological variables and the numerical achievement of elite players in intermediate distances, and also to try to determine the appropriate time to conduct it before the competition in intermediate distances. Study Design and application: We used a quasi-experimental method. The study was conducted on a purposive sample of fifteen runners from intermediate distances elites at West Bank-Palestine. In order to collect data of study variables we used three measurements, the first measurement was carried out before wet cupping, then the second measurement was carried out after three days of wet cupping, and the third measurement was carried out after five days of second measurement. Repeated measures of ANOVA was used to analyze data. Results: The study findings revealed that most physiological variables showed positive changes in all parameters with statistically significant differences between the three measurement means in favor of the last measurement. Also, the study showed positive changes in the record of running 1500 meter event with statistically significant differences between three measurement means in favor of the last measurement. Conclusion: wet cupping is effective to make appositive changes in physiologicalvariables and in the numerical achievement of the elite runners in the intermediate distances. The researchers recommend that wet cupping be performed at least seven days before the competition in intermediate distances.